2006
DOI: 10.1590/s0102-86502006000800005
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da cicatrização de suturas na bexiga urinária de ratos com e sem a utilização de extrato bruto de Jatropha gossypiifolia L. intraperitoneal

Abstract: RESUMO Introdução:A sutura dos tecidos e sua cicatrização é um dos fundamentos básicos da cirurgia e a procura de substâncias que melhorem este processo é desafio constante. O uso de substâncias retiradas de plantas tem sido testado há muitos anos, contudo sem ainda terem comprovação científica consolidada. Objetivo: Comparar as alterações macroscópicas e histológicas proporcionadas pelo uso do extrato bruto da Jatropha gossypiifolia L. intraperitonial, na cicatrização de suturas realizadas na bexiga urinária … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
(19 reference statements)
0
2
0
1
Order By: Relevance
“…Another study evaluated the healing action of the hydroethanolic crude extract from leaves of J. gossypiifolia in the healing process of sutures performed on the bladder of rats, and similar results were presented, although some improvement might have been observed in some parameters. In general, the authors concluded that no favorable healing effect was observed with the administration of single intraperitoneal dose of J. gossypiifolia L. [ 108 ]. In another study analyzing the morphological aspects of the healing process occurring in open skin lesions in rats under topical administration of raw extract from J. gossypiifolia (details about extract preparation and plant part not specified), the authors also observed an absence of healing action, although some histological improvement was shown [ 125 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Another study evaluated the healing action of the hydroethanolic crude extract from leaves of J. gossypiifolia in the healing process of sutures performed on the bladder of rats, and similar results were presented, although some improvement might have been observed in some parameters. In general, the authors concluded that no favorable healing effect was observed with the administration of single intraperitoneal dose of J. gossypiifolia L. [ 108 ]. In another study analyzing the morphological aspects of the healing process occurring in open skin lesions in rats under topical administration of raw extract from J. gossypiifolia (details about extract preparation and plant part not specified), the authors also observed an absence of healing action, although some histological improvement was shown [ 125 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Apenas um cão apresentou melhora cistométrica, e ela foi pouco duradoura, passados 60 dias pós transplante, o estado miccional retornou ao observado no período pré transplante, indicando a necessidade de outras infusões de células para melhora do quadro. Além disso, é preciso considerar que a incontinência por um longo período, gera maior grau de colagenização da bexiga urinária, o que impede boa dilatação e adequada complacência (Maia et al 2006, D' Ancona & Moro 2015.…”
Section: Quadro 2 Resultados Dos Exames Cistométricos Em Cães Com Leunclassified
“…Thanks to the advent of science, the human being starts to search new ways based on the biotechnology for wounds scarring 4 .…”
Section: Introductionmentioning
confidence: 99%